Diversifikasi Wortel Menjadi Puding Sebagai Upaya Mengatasi Anak Sulit Mengkonsumsi Sayur di Desa Situnggaling Kabupaten Karo - Moza Hanu Sabila; Fuja Adinda Sinaga; Miza Nina Adlini; Yenni Safitri; Nur Izzaty Rahma (Kampus Akademik Publiser, 2026)
Indonesia, as a tropical country, boasts a wide variety of plants, including vegetables and fruits, with carrots (Daucus carota L) being one of the majorly produced ones. Data from the Central Bureau of Statistics (BPS) indicates that in 2021, the harvest area of carrots reached 5,707 hectares, a 33.25% increase from the previous year, with Kabupaten Karo in North Sumatra being one of the regions with the largest carrot production. Carrots are known for their high content of beta-carotene and vitamin A, which are important for health. However, in Situnggaling Village, Kabupaten Karo, many children struggle to consume vegetables. To address this issue, a community service activity was conducted to introduce the making of carrot pudding as a healthy snack alternative. The activity utilized a demographic method involving outreach and training sessions. The results show that participants were highly enthusiastic and successfully learned how to process carrots into pudding, which is enjoyed by both children and adults. The activity also provided additional economic benefits for housewives. In conclusion, this project represents an effective and creative solution for increasing vegetable consumption among children and offers a practical and appealing approach to addressing vegetable consumption issues.